2017
DOI: 10.1590/s0100-736x2017000200015
|View full text |Cite
|
Sign up to set email alerts
|

Perfil metabólico de vacas Jersey clinicamente saudáveis

Abstract: RESUMO.-O conhecimento do metabolismo dos animais é de suma importância para se obter sucesso em qualquer atividade que envolva rebanhos. Objetivou-se determinar o perfil bioquímico sérico de vacas Jersey clinicamente saudáveis no pré e pós-parto, mantidas em sistema de criação semi-intensivo na região de Uberlândia, Minas Gerais, Brasil. Realizou-se o exame clínico e coleta de sangue de 40 vacas da raça Jersey multíparas e lactantes em 15 momentos, entre -150 dias pré-parto até 60 dias pós-parto (DPP). No lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
3
3
0
2
Order By: Relevance
“…However, we do not believe this is the reason because the alteration occurred only in Experiment I. GGT and AST activity did not change between groups, a positive result demonstrating that the use of cracker residue does not cause liver damage in animals. Alvarenga et al [34] showed that AST activity oscillated between 73.05 and 102.41 U/L and GGT activity between 16.15 and 9.93 U/L for clinically healthy Jersey cows, similar to our work.…”
Section: Discussionsupporting
confidence: 91%
“…However, we do not believe this is the reason because the alteration occurred only in Experiment I. GGT and AST activity did not change between groups, a positive result demonstrating that the use of cracker residue does not cause liver damage in animals. Alvarenga et al [34] showed that AST activity oscillated between 73.05 and 102.41 U/L and GGT activity between 16.15 and 9.93 U/L for clinically healthy Jersey cows, similar to our work.…”
Section: Discussionsupporting
confidence: 91%
“…Em estudo recente quanto ao perfil metabólico de vacas Jersey, a hipocalcemia subclínica foi frequente, ocorrendo em 57,1% dos animais no pré-parto e 76,2% no pós-parto. Tem sido atribuída à raça Jersey maior tendência para a hipocalcemia relacionada com menor absorção intestinal, porém, segundo os autores, a hipocalcemia observada teria relação com os valores de albumina que permaneceram próximos ao limite mínimo de referência no período (23) . Não foram encontrados estudos semelhantes com animais Jersolando, e o presente estudo sugere maior adaptação da raça ao manejo adotado nas propriedades de agricultura familiar.…”
Section: Resultsunclassified
“…However, these clinical conditions would also correspond with similarly low TPP and PCV levels, which we did not observe. Peripartum cows raised under Brazilian conditions tend to have low ALB levels (ALVARENGA et al, 2017;BIRGEL JUNIOR et al, 2003) that are lower than the international reference values (FÜRLL, 2005;SMITH, 2009), which led Alvarenga et al (2017) to advocate the use of lower national reference values, at least in this stage. It should, however, be noted that we detected no significant differences in ALB when comparing the MIP and SIP groups.…”
Section: Discussionmentioning
confidence: 99%